3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 07:43:52
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)左右两边都乘以
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
左右两边都乘以12
4(5y+4)+3(y-1)=24-(5y-5)
20y+16+3y-3=24-5y+5
23y+13=29-5y
28y=16
y=4/7
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
3分之(5y+4)+4分之(y-1)=2-12分之(5y-5)
三分之y加4-y+5=三分之y+3-二分之-y-2
解方程:3y-6分之3y+5=2分之1+ 2y-4分之5y-4
(3y-6)分之(2y+5)=(2y-4)分之(5y-4)+2分之1
y方+y分之y+3-1-y分之1=y分之4很急,
y*(6分之5+8分之5)=20分之7 3分之2y-4分之1y=6分之1 y-7分之2y=14分之1x*(6分之5+8分之5)=20分之7 3分之2x-4分之1x=6分之1 x-7分之2x=14分之1
{x分之2-y分之3=4,x分之3+y分之6=5
2分之x+3分之y=7 3分之x-4分之y=-1
y-5分之1=3分之2 15分之7+y=60分之37 5分之4-y=40分之17 6分之1+y =9分之8-3分之1y-5分之1=3分之2 15分之7+y=60分之37 5分之4-y=40分之17 6分之1+y =9分之8-3分之1
(y+1)分之(2y+3)=(3y+4)分之(6y+7)
(3分之5y+4)+4分之y-1=2-12分之5y-5要过程
3分之5y+4+4分之y-1=2-12分之5y-5怎么做?
解方程:3分之5y+4+4分之y-1=2-12分之5y-5
3分之(5y+4)+4分之(y减1)=2-12分之(5y减5) 解方程
解方程组{2分之x-3分之y=5,4分之x+5分之y=1
3分之x-2y=4分之2x-3y-1=6分之5x-y+2
{3分之x减2分之y=1,3分之x减4分之y=5 解方程,